Development of a Web-Based Printing Service Application Using the Waterfall Model - Susila, Mochamad Nandi; Haryanto, Haryanto; Fridayanthie, Eka W; Budiyono, Pungkas (Sean Institute, 2025)
The rapid growth of the creative industry has increased the demand for printing services that are fast, accurate, and consistent in quality. However, many printing businesses still rely on manual operational processes, including order recording, design verification, cost estimation, and production monitoring. These limitations often result in delays, miscommunication with customers, and difficulties in tracking incoming orders. This study focuses on the development of a web-based information system designed to automate the ordering process and enhance communication between customers and printing service providers. The system was developed using the Waterfall model, which consists of requirement analysis, system design, implementation, testing, and maintenance. Data were collected through field observations and interviews with the owner of a local printing business. The results indicate that the developed system provides online ordering features, design file uploads, automatic cost estimation, job status tracking, and real-time process update notifications. The implementation of this system not only improves production efficiency but also reduces recording errors and enhances customer satisfaction. This web-based solution is expected to support the digital transformation of printing service businesses in the modern industrial era.